PERLINDUNGAN HUKUM HUMANITER TERHADAP PEREMPUAN DARI KEKERASAN SEKSUAL DALAM SENGKETA BERSENJATA - Hilda, Hilda (LPPM Unisba, 2010)
The sexual violence against women in armed conflict has been admitted as the intentionally and systematic violence, and even tended to be part of the war strategy by combatants. Â Afterwards, legal protection on such violence became very important to be given not only in peacetime but also in war time. Under some international legal instruments related to the humanitarian legal protection i.e. the Geneva Convention of 1949, additional Protocol of 1977, and other supplementary legal instrument including human rights legal instruments, sexual violence carried out in armed conflict was categorized as war crime and crime against humanity.